Domestic funding for health policy and systems research: why is it invisible? - Geetanjali Lamba; Livia Dal Zennaro; Solip Ha; Sonam Yangchen (Sax Institute, 2021)
Objectives and importance of study: Health policy and systems research (HPSR) informs stronger health systems but it remains chronically underfunded, especially in low- and middle-income countries (LMICs). Domestic funding for HPSR helps to ensure research is aligned with local priorities. As LMICs transition from international donor assistance for health research, HPSR will increasingly need to rely on domestic funding. However, domestic funding flows remain poorly understood. This study aims to understand how, and how much, HPSR is funded domestically in LMICs. It explores challenges associated with estimating HPSR funding and suggests strategies to improve domestic support for HPSR. Study type: Mixed methods. Methods: We reviewed regional technical reports commissioned by the Alliance for Health Policy and Systems Research, which studied domestic HPSR funding through desk reviews and key informant interviews. Data were qualitatively and quantitatively analysed and findings were triangulated. We also conducted a separate bibliometric analysis to understand HPSR capacity. Results: Despite many efforts from different angles, we were unable to reliably estimate HPSR funding in most of the countries studied. The reasons for this included a lack of a common understanding of HPSR, difficulty disentangling HPSR funding from other research funding, and bureaucratic and data transparency hurdles. We also describe which domestic bodies fund HPSR and examine the interrelatedness of HPSR capacity and funding. Conclusion: Domestic funding flows for HPSR remain almost invisible. This finding informs concrete recommendations to improve HPSR funding transparency, and for national research funders and ministries of health and finance to invest in HPSR for stronger health systems.